2010
DOI: 10.1080/03004430903450392
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brief interventions on the drinking behaviour of pregnant women in a high‐risk rural South African community: a cluster randomised trial

Abstract: The purpose of this paper is to assess the impact of a series of brief interventions (BIs) on anti-natal alcohol consumption of women from a disadvantaged and highrisk background attending state health clinics in a rural district, Western Cape Province, South Africa. A pragmatic cluster randomised trial design was followed. All pregnant women, who were less than 20 weeks pregnant and more than 15 years of age, were eligible for the study. The intervention comprised a comprehensive assessment for current and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 15 publications
1
59
1
Order By: Relevance
“…Recent reviews of interventions in educational settings to reduce the harm associated with adolescent substance use outlined the positive potential of brief alcohol intervention with young people (Toumbourou et al, 2007;Carney and Myers, 2012;Mitchell et al, 2013). Individual studies also show effect in emergency departments and general hospital wards (Nilsen et al, 2008;McQueen et al, 2011) and with pregnant women within antenatal care (O'Connor and Whaley, 2007;Marais et al, 2011).…”
Section: Brief Interventionsmentioning
confidence: 99%
“…Recent reviews of interventions in educational settings to reduce the harm associated with adolescent substance use outlined the positive potential of brief alcohol intervention with young people (Toumbourou et al, 2007;Carney and Myers, 2012;Mitchell et al, 2013). Individual studies also show effect in emergency departments and general hospital wards (Nilsen et al, 2008;McQueen et al, 2011) and with pregnant women within antenatal care (O'Connor and Whaley, 2007;Marais et al, 2011).…”
Section: Brief Interventionsmentioning
confidence: 99%
“…Finally, one study found that women in antenatal care receiving brief interventions were significantly less likely than women receiving no treatment to have an infant with low birth weight or to suffer preterm labor problems, while another study found positive effects of brief intervention on prenatal drinking in women with higher initial rates of consumption [22,23]. Most recently, a trial of brief interventions in antenatal clinics in South Africa found that women who received a brief intervention had significantly greater reductions in scores on the Alcohol Use Disorders Identification Test (AUDIT) screening tool [27] by their third trimester, compared with women receiving assessment only [28]. Taken together, this evidence suggests that brief intervention is a promising approach for alcohol risk reduction in antenatal care.…”
Section: Introductionmentioning
confidence: 99%
“…Despite effective treatments for mental health and substance use disorders (Baker et al, 2010;Marais et al, 2011;May et al, 2013;Meyer, Johnston, Crocker, & Heil, 2015), only 10.3% to 39% of pregnant women with these complex health issues receive treatment (Cook et al, 2010;Glasheen, Colpe, Hoffman, & Warren, 2015;Le Strat et al, 2011, Rosen, Tolman, & Warner, 2004Song, Sands, & Wong, 2004;Vesga-Lopez et al, 2008 (Ondersma, Simpson, Brestan, &Ward, 2000), making prenatal substance use a significant public health problem.…”
Section: Recommendationsmentioning
confidence: 99%
“…On the other hand, this may indicate that pregnant women did not access treatment until the severity of their substance use became paramount, suggesting a delayed access to treatment due to numerous barriers (CSAT, 2009). Given that alcohol abuse was the most common substance use disorder among pregnant women in the current study, screening and brief intervention are recommended to help pregnant women decrease antenatal alcohol consumption (Marais et al, 2011).…”
Section: Need Factors Predicting Treatment Receiptmentioning
confidence: 99%
See 1 more Smart Citation